Internalizing Struggle Values in Pesantren Education at TMI Al-Amien Prenduan - Ach. Nurholis Majid; Ahmad Efendi Aliansyah (Penerbit Hellow Pustaka, 2026)
This study explored (1) the meaning of struggle values (nilai-nilai kejuangan) in pesantren education and (2) how these values were internalized within the educational system of TMI Al-Amien Prenduan. Using a qualitative field approach, data were collected through in-depth interviews, observation, and document analysis involving key institutional figures and educators. The findings indicate that struggle values at TMI Al-Amien Prenduan are primarily oriented toward worship (ibadah) and dedicated service (pengabdian) in education, conceptualized through the ethos of mujāhid al-tarbiyah (educational striver). These values are characterized by sincerity (ikhlas), doing one’s best, total commitment, and integrity in fulfilling educational responsibilities. The internalization process occurs in three interconnected stages: value transformation (value transmission and orientation), value transaction (two-way interaction and exemplary modeling), and transinternalization (habit formation and personality embodiment through the 24-hour pesantren system). The study highlights the uniqueness of institutional value formation where devotion, discipline, and continuous guidance are embedded into daily life, shaping educators and students into committed members of a value-based educational community.